Spinal neurocysticercosis diagnosed by lumbar puncture - Huamaní, Charles (2018)
Neurocysticercosis is a frequent disease, its main location is in the brain parenchyma; however, less than 5% of cases are of spinal location where they produce pseudotumoral or obstructive clinical manifestations. We present the case of a patient admitted due to chronic headache with signs of endrocranial hypertension, without clinical symptoms, and in whom a cysticercotic membrane and cerebrospinal fluid with high glucose consumption (3mg/dL) was obtained during the lumbar puncture study. The finding of a cysticercus of intradural-extramedullary location, during a lumbar puncture is a very rare finding, only described in patients with evident clinical signs. We recommend suspecting it when there is no clinical evidence of spinal cord involvement but there is a suggestion of cerebral cysticercosis and altered cerebrospinal fluid, expanding the study with neuroimaging.